The Mineral Characteristic of Tropical Residual Soil using X-Ray Diffraction (XRD) and Scan Electron Microscopy (SEM) - Rinda Karlinasari; Paulus P. Rahardjo; Azis Dajaputra (Universitas Islam Sultan Agung, 2023)
Volcanic residual soil has unique characteristics due to weather and morphological influences. High temperatures and large amounts of rainfall made the rock weathering intense. Landslide events in volcanic residual soil of West Java are quite serious, more than 100 incidents in total a year. Landslides that occur due to unsaturated conditions on the top of the slope become saturated, so it is very important to conduct research on these tropical residual soil weathering zones to define its mineral characterization using Scan Electron Microscopy (SEM) and X-Ray Diffraction (XRD). From the research it was found that the dominant mineral types and contents were Halloysite and Kaolinite minerals. A typical mineral profile is found that is Goethite and Hematite minerals at the soil surface, Carbonate and Chlorite minerals in deeper soils and large amounts of Feldspar minerals in more deep layers. Because there are unique minerals at each depth of soil weathering, zone classification can be done easily starting from the Initial Leaching Zone at the deepest part where there is Feldspar, the Mineral Washing Zone there is Carbonate and Chlorite and the Oxidation Zone on the surface (there are Oxide and Hydroxide minerals). So that it can form a Residual Tropical Volcanic Weathering Profile.